The University and City Images for Migration of Nonresident Students: a Regional Case - G. F. Gabdrakhmanova (Высшее образование в России, 2023)
The global digital transformation of the economy requires a new look at the information basis for making managerial decisions on the problem of uneven distribution of universities across Russian regions. It involves the creation of a data bank on key issues of Russian higher education. One of these indicators may be the subjective reasons for the attractiveness of territories for applicants/students/graduates in terms of the significance of images of the university and city of study, as well as factors influencing educational migration. The goal is to show, using the example of a separate case, the role played by the images of the university and the city in the choice of a university, adaptation and postgraduate migration of students from other cities (coming from Russian cities and villages). The theoretical framework of the study is built by synthesizing the theories of “spirals” about the third function of higher education, and the theory of the image of the territory in relation to educational migration. The analysis involves statistical data on the socio-economic situation in Russian regions that attract educational migrants, and the results of a survey of out-of-town students of Kazan Federal University.The study found that both the university and the city are equally important bases for educational strategies for the majority of applicants. During their studies, they, like those who came to study only because of the university or just because of the city, consolidate the image of Kazan as a student territory with rich infrastructure and quality life, a sense of belonging to the capital of Tatarstan, positive assessments and a desire to recommend it to friends for moving. However, the reasons for educational migration and the perception of Kazan do not affect the postgraduate plans of students. Regions that are able to attract applicants and retain students after graduation – Moscow and the Moscow region, St. Petersburg and the Leningrad region, Sverdlovsk and Novosibirsk regions – benefit from Tatarstan due to the fact that they offer more favorable living conditions and a larger range of offers on the market work for young professionals.The practical significance of the work lies in the position on the importance of combining the policies of shaping the images of the university and the city, not only to attract talented youth, but also to improve the third mission of Russian universities in terms of their inclusion in the development of urban activities among students, the use of the intellectual potential of higher education for socio-economic development of territories.